Lycopodina calyx - Ekins, Merrick; Erpenbeck, Dirk; Hooper, John N. A. (Zenodo, 2020)
Lycopodina calyx (Hentschel, 1914) Fig. 26, Tables 14 & 15 Asbestopluma calyx Hentschel, 1914: 66, Pl. IV, Fig. 4, PL. V, Fig. 11; Burton 1932: 293; Burton 1934: 24; Koltun 1964: 32, Pl. V, Figs 8–12. Asbestopluma (Asbestopluma) cf. calyx: Lopes & Hajdu 2014: 333, Fig. 3. Lycopodina calyx: Goodwin et al. 2017: 54, Fig. 11; Dressler-Allame et al. 2017: 200, Fig. 13. Material examined : QM G337513 off Central New South Wales, Tasman Sea, Station 88, New South Wales, Australia, 30° 15’ 50.4”– 30° 17’ 12.1” S, 153° 52’ 12”– 153° 49’ 48.7” E, 4481– 4401 m, Beam Trawl, Coll. Merrick Ekins on RV Investigator , Cruise IN2017_ V03, Sample 88-141, 2 specimens, 6/vi/2017. QM G337463 same collection details as QM G337513, Sample 88-141.2. QM G337476, off Gippsland, Tasman Sea, Station 33, Victoria, Australia, 38° 31’ 15.6”– 38° 29’ 52.8” S, 150° 12’ 46.8”– 150° 12’ 25.2” E, 4107– 4064 m, Brenke epibenthic Sledge, Coll. Merrick Ekins on RV Investigator , Cruise IN2017_ V03, Sample 33-156, 24/v/2017. SAMA S314, off Kaiser Wilhelm Land, Antarctica, BANZARE Station 100, 65° 48’ S, 89° 49’ E, 393 m, large rectangular dredge, Coll. BANZARE, 3/v/1931. Mycalostyles 621-(1364)-1816 x 7-(19)-33 Subtylostyles 202-(285)-328 x 4-(5)-8undifferentiatedunknownpalmate anisochelae (11-(13)-15 x 2-(3)-5absentabsentOff Moreton Island, Queensland, Australia, abyssal .Continued on the next page palmate anisochelae 11–16 x 5–8Sigmancistras 9–1130–51 x 3–11Great Australian Bight, bathyal .Continued on the next page undifferentiatedundifferentiatedpalmate anisochelae 9–22 x 4–9 (10–14) [11–13]absentabsentWilkes Land, Willhem II Coast & Drake Passage, Antarctica, mesophotic- abyssal .Continued on the next page axial mycalostyles, 440–510 x 11–12subtylostyles 1, 238–476 x 7–8 subtylostyles 2, 149–230 x 5–7 polytylote styles 3, 700–1400 x 5unknownarcuate to palmate anisochelae, 17–19absentabsentReykjanes Ridge, N Atlantic, bathyal .Continued on the next page up to 100 x 40Axis with longitudinally arranged styles, with single styles ...